2016
DOI: 10.1136/bmjopen-2016-011653
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the accuracy of parentally reported weights and lengths at 12 months of age as compared to measured weights and lengths in a longitudinal childhood genome study

Abstract: BackgroundChildhood obesity studies rely on parentally reported anthropometrics. However, the accuracy of such data has not been evaluated for 12-month-old children. Moreover, methods to improve the accuracy of reported data have not been assessed in prior studies.MethodsA total of 185 children enrolled in a northern Virginia childhood longitudinal cohort genomic study had parentally completed surveys at 12 months. Measured weights and lengths were recorded for the same children from their 12-month paediatrici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Additionally, anthropometrics used were parent reported, which are known to have varying reliability. While measured anthropometrics were preferred, the accuracy of parent-reported anthropometrics was improved in this study by the removal of outliers, which has been previously validated in this cohort [28].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Additionally, anthropometrics used were parent reported, which are known to have varying reliability. While measured anthropometrics were preferred, the accuracy of parent-reported anthropometrics was improved in this study by the removal of outliers, which has been previously validated in this cohort [28].…”
Section: Discussionmentioning
confidence: 95%
“…Gestational weight gain recommendations were categorized into: "lower than recommended range", "within recommended range," and "greater than recommended range" [27]. Parentally reported anthropometrics for infants at 12 months of age were recorded, outliers were removed for reported lengths using the interquartile range, and weight for length percentiles (WFLP) at 12 months were calculated with the World Health Organization sex-specific growth charts, as previously validated in this cohort [28]. In this study, excess weight was defined as WFLP ≥ 95th% and risk for excess weight as WFLP ≥ 85th%.…”
Section: Subjects and Sample Collectionmentioning
confidence: 99%
“…Anthropometrics for the children with FASDs were caregiver-reported measurements, which included the children's birth weight, current weight, and current height. Anthropometric measurements of children through maternal, parent or caregiver-reported surveys have been evaluated in other published studies and found to be appropriate for birthweight and in weight for length percentiles when outliers were removed [30,31]. Birthweight was categorized as a low birthweight of <2.5 kg.…”
Section: Children Anthropometric Measurementsmentioning
confidence: 99%
“…The First 1000 Days and Beyond (F1000 or FTDL) study is a longitudinal pregnancy cohort of mother-child pairs living in Virginia. 20,21 Women were ≥18 years of age and willing to participate participate between 2016 and 2021. 22,23 A total of 708 mother-child pairs with complete data on birth information also consented for biospecimen collection including urine for metal assays.…”
Section: Scenariomentioning
confidence: 99%